Designing multifunctional urban agroforestry with people in mind. Issue 1 (6th August 2021) - Taylor, John R.; Lovell, Sarah Taylor
Abstract: Urban landscapes combining trees and crops—urban agroforestry (UAF) systems—may offer greater ecological and cultural benefits than annual cropping systems. Interest in UAF is growing, as evidenced by an increasing number of built projects and articles in the popular press and the academic literature on the subject. However, the practice of UAF appears to far outpace research on its scientific underpinnings or its design. Developing sustainable, resilient UAF sites can be challenging because of biophysical and sociocultural conditions unique to the city; however, cities offer opportunities not found in rural environments including the potential to close open nutrient loops between consumers and sites of food production. We argue that these biophysical and sociocultural challenges and opportunities can be best addressed through an evidence‐based approach to the design of UAF systems and a complex ecological aesthetic design language integrating theory, principles, and practices from urban agroecology and allied fields, environmental psychology, and landscape architecture. The resulting multifunctional UAF systems would be socially sustainable and equitable and promote the circular metabolism of the city. Drawing on a purposive review of literature from these disciplines, we propose a preliminary framework consisting of 14 guidelines and complementary principles and strategies for the design of multifunctional, culturally preferred UAF and offer recommendations for future research. Core Ideas: The practice of urban agroforestry (UAF) outpaces research on system science and design. A system‐specific complex ecological aesthetic design language could enhance multifunctionality. Evidence‐based design guidelines, principles, and strategies can inform UAF practice. Additional research is needed to bridge the gap between practice and theory.